Planning Allocation for GTO-GEO Transfer Spacecraft with Triple Orthogonal Gimbaled Thruster Boom - Ma, Guangfu; Kong, Xianglong (Mathematics (Basel), 2023)
This paper proposes an electric propulsion platform based on a triple orthogonal gimbaled thruster boom to realize the GTO-GEO transfer process. The adjustment mechanism of the gimbaled thruster boom significantly improves the range of thrust vector variation enhances the efficiency of thrust vector adjustment, and reduces the spacecraft burn-up. Additionally, to achieve the application performance, a planning allocation method based on the model prediction algorithm is proposed and verified through numerical simulation.